Redesigning Work: A Student-Learning Initiative for Safer and Smarter Ergonomic Carts - Avila, Sharmaine M; Arago, Ryan F; Dellova, Rovena I; Fonollera, Eldrick M; Lare, Marry Sol L (Logistic and Operation Management Research (LOMR), 2025)
Ergonomic carts improve safety, reduce strain, and enhance efficiency, but their real-world impact remains unseen. This service-learning initiative, driven by students, aims to assess the impact of ergonomic carts on comfort, usability, and musculoskeletal disorders, providing insights to refine user-centered designs and improve operational outcomes. An exploratory sequential mixed-methods approach using purposive sampling was employed to gather data from 14 qualified beneficiaries.  The study evaluated key aspects such as productivity, carts’ durability, and ergonomic benefits, and how these features influence the overall user experience. Data were analyzed using weighted mean and standard deviation while maintaining ethical standards. Most respondents were women, aged 41-60, highlighting the cart's relevance for age-related impairments. Daily use indicated ergonomic benefits, improved productivity, time management, and comfort, with high durability and adaptability scores. The cart reduced musculoskeletal pain, improved posture, and decreased fatigue. Participants also noted cost savings, reduced waste, and improved community organization. The study’s scope was limited to specific demographic groups, suggesting the need for broader future research. This study highlights the importance of ergonomic interventions in workplace tools and advocates for user-centered designs that enhance well-being and productivity. To address Sustainable Development Goals 1, 3, 8, and 12, this study promotes inclusive economic growth, healthier work environments, and sustainable practices.